2009
DOI: 10.1109/tmi.2009.2017375
|View full text |Cite
|
Sign up to set email alerts
|

Design, Construction, and Testing of a Stereo-Photogrammetric Tool for the Diagnosis of Fetal Alcohol Syndrome in Infants

Abstract: Stereo-photogrammetry provides a low cost, easy to use, and noninvasive alternative to traditional facial anthropometry for the diagnosis of fetal alcohol syndrome (FAS). We describe such a system for use in obtaining 3-D facial information in infants. The infant is photographed using three high resolution digital cameras simultaneously while seated in a car seat. The subject's head is enclosed in a control frame during imaging. Technical system tests, namely control frame interpolation, camera calibration rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 34 publications
0
31
0
1
Order By: Relevance
“…The calibration frame is fitted with retro‐reflective markers of known 3D coordinates. Using these markers, the camera calibration parameters and a bundle adjustment algorithm, the 3D coordinates of any point within the defined volume of the calibration frame can be obtained to a high degree of accuracy [Mutsvangwa et al, 2009].…”
Section: Methodsmentioning
confidence: 99%
“…The calibration frame is fitted with retro‐reflective markers of known 3D coordinates. Using these markers, the camera calibration parameters and a bundle adjustment algorithm, the 3D coordinates of any point within the defined volume of the calibration frame can be obtained to a high degree of accuracy [Mutsvangwa et al, 2009].…”
Section: Methodsmentioning
confidence: 99%
“…A recent study evaluated the effect of pose on the reliability of stereophotogrammetric measurements for quantitative assessment of facial geometry for the diagnosis of fetal alcohol syndrome. 25 They found that for facial imaging it was not only important to obtain images while the subject was in the correct pose but it was critical that all cameras in the stereophotogrammetric system capture images at the same instant. However, there are no studies to date that have addressed this issue for 3D imaging of the human torso.…”
Section: Discussionmentioning
confidence: 99%
“…These studies lead to the development of a reliable device for anthropometric measurements for small infants. Mutsvangwa et al [128] showed that these measurements can provide different accuracy for discriminating subjects affected by the symptoms depending on the age. Thus, the accuracy of the method for 5 years old subjects reaches 95.46%, while the rate decreased to 80.13% for 12 years old subjects.…”
Section: Neurologic Conditions and Neurodevelopmental Disordersmentioning
confidence: 99%